Ecofeminist Empowerment: In Preserving the Musi River Waters of Palembang City in 2023 - Melinda, Melinda; Sanny Nofrima, Sanny Nofrima; Alam Mahadika, Alam Mahadika (JOURNAL OF GOVERNMENT SCIENCE, 2025)
This article discusses ecofeminist empowerment in efforts to conserve the waters of the Musi River in Palembang City in 2023. This research takes an ecofeminist approach by combining environmental and gender perspectives, focusing on the understanding that human relationships with nature have complex social and cultural dimensions. This research used a qualitative approach involving interviews and observations. The data collected were thematically analyzed to explore the understanding of ecofeminist contributions to the preservation of the waters of the Musi River. The results showed that the ecofeminist approach has made an important contribution to the efforts to conserve the waters of the Musi River. However, several factors that influence ecofeminist empowerment still need to be addressed. Social and cultural factors, such as gender stereotypes and limited roles for women in environmental affairs, are obstacles in increasing women’s active participation in water conservation. In addition, inadequate policies and regulations also need to be considered to create a supportive environment for ecofeminist empowerment. In this context, collaborative efforts need to be made between the government and civil society to overcome these problems. It is hoped that the results of this research can make a significant contribution to efforts to conserve the waters of the Musi River in Palembang City, while strengthening awareness of the link between the environment and gender.